China dolls ebook A novel. - See, Lisa (2014)
NEW YORK TIMES  BESTSELLER • “A fascinating portrait of life as a Chinese American woman in the 1930s and ’40s.”— The New York Times Book Review   “Superb . . . This emotional, informative and brilliant page-turner resonates with resilience and humanity.”— The Washington Post  (One of the Best Books of the Year)    San Francisco, 1938: A world’s fair is preparing to open on Treasure Island, a war is brewing overseas, and the city is alive with possibilities. Talented Grace, traditional Helen, and defiant Ruby, three young women from very different backgrounds, meet by chance at the exclusive and glamorous Forbidden City nightclub. The girls become fast friends, relying on one another through unexpected challenges and shifting fortunes. When their dark secrets are exposed and the invisible thread of fate binds them even tighter, they find the strength and resilience to reach for their dreams. But after the Japanese attack Pearl Harbor, paranoia and suspicion threaten to destroy their lives, and a shocking act of betrayal changes everything.   Praise for  China Dolls   “A sweeping, turbulent tale of passion, friendship, good fortune, bad fortune, perfidy and the hope of reconciliation.” — Los Angeles Times   “Bravo! Here’s a roaring standing ovation for this heartwarming journey into the glittering golden age of Chinese nightclubs.” —Jamie Ford, author of  Hotel on the Corner of Bitter and Sweet   “Lisa See masterfully creates unforgettable characters that linger in your memory long after you close the pages.” — Bookreporter   “Stellar . . . The depth of See’s characters and her winning prose make this book a wonderful journey through love and loss.” — Publishers Weekly  (starred review)